Polymers for PEM fuel cells - Pu, Hongting (Wiley, 2015)
Includes chemical, synthetic, and cross-disciplinary approaches; this book includes the necessary techniques and technologies to help readers better understand polymers for polymer electrolyte membrane (PEM) fuel cells. The methods in the book are essential to researchers and scientists in the field and will lead to further development in polymer and fuel cell technologies. Provides complete, essential, and comprehensive overview of polymer applications for PEM fuel cells Emphasizes state-of-the-art developments and methods, like PEMs for novel fuel cells and polymers for fuel cell catalysts.